English teacher identity: experiences into the supervised internship - RODRIGUES, Josymara Gabriele Sousa (2024)
This article presents perceptions about the concepts of teacher identity and reflections on how the supervised internship is one of the main elements for this identity construction. To this end, it relies on the theoretical framework composed by Hall (2006) with regard to understanding the construction of identity in a globalized context. It also draws on the analyses of authors such as Flores (2015), Gaignoux (2020), Reis, Van Veen and Gimenez (2011) on the fundamental elements for the construction of teacher identity. Likewise, discussions on supervised internships will be guided by Pimenta and Lima (2011). Next, based on the studies of the aforementioned authors, I share personal accounts of my experiences and reflections on how the internship played an important role in my construction and reconstruction as an English teacher. Firstly, I discuss concepts related to the construction of teacher identity and its main constituent elements, as well as the importance of the internship and its relevance to the training of future teachers. Finally, I present my accounts of my internship experiences and how they have contributed to my development as a teacher. This is a qualitative study based on bibliography and documents. Considering all the concepts and discussions covered in this work, we concluded that the supervised internship is one of the main elements in the formation, construction and reconstruction of the teacher's identity.